Co-generation of hydrogen and power/current pulses from supercapacitive MFCs using novel HER iron-based catalysts. (1st December 2016) - Santoro, Carlo; Soavi, Francesca; Arbizzani, Catia; Serov, Alexey; Kabir, Sadia; Carpenter, Kayla; Bretschger, Orianna; Atanassov, Plamen
Highlights: Supercapacitive MFC boosted up power/current pulses. In-series connection of 4 microbial fuel cells quadrupled voltage and power output. Fe-catalysts showed high hydrogen evolution reaction rate in neutral media. Co-generation of electricity and hydrogen using SC-MFCs is here demonstrated. Abstract: In this work, four different supercapacitive microbial fuel cells (SC-MFCs) with carbon brush as the anode and an air-breathing cathode with Fe-Aminoantipyrine (Fe-AAPyr) as the catalyst have been investigated using galvanostatic discharges. The maximum power (Pmax ) obtained was in the range from 1.7 mW to 1.9 mW for each SC-MFC. This in-series connection of four SC-MFCs almost quadrupled Pmax to an operating voltage of 3025 mV and a Pmax of 8.1 mW, one of the highest power outputs reported in the literature. An additional electrode (AdHER ) connected to the anode of the first SC-MFC and placed in the fourth SC-MFC evolved hydrogen. The hydrogen evolution reaction (HER) taking place at the electrode was studied on Pt and two novel platinum group metal-free (PGM-free) catalysts: Fe-Aminoantipyrine (Fe-AAPyr) and Fe-Mebendazole (Fe-MBZ). The amount of H2 produced was estimated using the Faraday law as 0.86 mMd −1 cm −2 (0.132 L day −1 ) for Pt, 0.83 mMd −1 cm −2 (0.127 L day −1 ) for Fe-AAPyr and 0.8 mMd −1 cm −2 (0.123 L day −1 ) for Fe-MBZ. Hydrogen evolution was also detected using gas chromatography. While HER was taking place, galvanostatic discharges were also performed showing simultaneous H2 production and pulsed power generation with no need of external power sources.